Dodsworth in Rome - Egan, Tim, 1957- (Houghton Mifflin Harcourt, 2011)
Dodsworth and his duck companion have a lovely time in Rome, even though the duck tries to improve the ceiling of the Sistine Chapel and takes all the coins from the Trevi Fountain.